Direct medical cost analysis in the treatment of chronic kidney disease at Thong Nhat Dong Nai General Hospital in 2024 - Giang, Tran Ngoc Truong; Khanh, Tran Nguyen Mai; Vy, Pham Ngoc Bao; An, Tran Tien; Man, Tieu Tu; Nhi, Vo Ngoc Yen (Tạp Chí Khoa học Trường Đại học Quốc tế Hồng Bàng, 2025)
Background: Chronic kidney disease (CKD) is rapidly becoming more prevalent among younger populations, posing significant impacts on health and socio-economic development. Therefore, analyzing direct medical costs (DMCs) in CKD treatment is essential. Objective: To analyze DMCs in the treatment of CKD at Thong Nhat Dong Nai General Hospital in 2024. Subjects and Methods: A cross-sectional descriptive study was conducted using retrospective electronic billing data of all CKD patients who met the sampling criteria at Thong Nhat Dong Nai General Hospital from January to December 2024. Results: The study analyzed data from 7,634 patients, with a mean age of 63.41 ± 13.76 years. Among them, 24.18% were diagnosed with stage 1 CKD. The average annual DMC per patient, per inpatient episode, and per outpatient visit was 14.02 million VND (95% CI: 13.28-14.77 million VND), 10.81 million VND (95% CI: 9.76-11.85 million VND), and 3.45 million VND (95% CI: 3.38-3.53 million VND), respectively. The majority of the costs were reimbursed by health insurance (ranging from 89.30% to 93.06%). Factors associated with DMCs included gender, CKD stage, insurance reimbursement rate, type of insurance coverage, and the presence of vascular comorbidities. Conclusion: The annual DMCs for CKD treatment were estimated to account for approximately 12.3% of the national GDP per capita in 2024, with inpatient DMCs representing around 9.48% and outpatient DMCs accounting for approximately 3.03%.